Denitrifying sulfide removal by Pseudomonas sp. C27 at excess carbon supply: Mechanisms. (March 2015) - Guo, Hongliang; Chen, Chuan; Lee, Duu-Jong; Wang, Aijie; Ren, Nanqi
Highlights: Mixotrophic growth tests of C27 were conducted at different C/N ratios. At C/N = 1.63, C27 enhanced heterotrophic denitrification pathway. At C/N = 3.0, C27 accelerated metabolism via coupled-cycles pathway. With the coupled-cycles pathway, the accessible regime for C27 is enlarged. Revision of the coupled-cycles pathway was made. Abstract: Pseudomonas sp. C27 can effectively conduct mixotrophic denitrifying sulfide removal (DSR) reactions using both organic matters and sulfide as electron donors. This study conducted DSR tests using C27 and quantitatively analyzed the protein abundances at C/N = 1.26, 1.63 and 3.0. At C/N = 1.26, C27 principally adopted autotrophic denitrification pathway in DSR reaction. As C/N ratio was increased to 1.63, C27 enhanced heterotrophic denitrification pathway for removing nitrous compounds. As the C/N ratio was further increased to 3.0, C27 accelerated metabolism via coupled-cycles pathway. The C/N ratio for coupled-cycles pathway was estimated ranging 2.0–2.3 in the studied medium. Optimal C/N ratio of traditional DSR processes ranged 1.05–1.26. With the coupled-cycles pathway, the accessible C/N/S regime for C27 on DSR reactions is enlarged. Minor revision of the coupled-cycles pathway considering production of ammonium step was made.